THE NEW GREAT POWERS COMPETITION: A STRATEGIC ANALYSIS (Khairulummah, 2023)
Competition and adversarial relations among great powers on international stage is not a new Phenomenon. Every state wants to dominate other and established their hegemony over the rest of the world. It is Political, Economic, Technological and Geo-Strategic capabilities and Cultural Identity of State, which determine the rise or the resurgence of new Competitor in global arena. It is arguing that, Competition among states started, when a particular state Challenges the status-quo. However, the term ‘Great Power Competition’ was mainly associated with the Power struggle between USA and USSR after the end of World War II. The rivalry ended with the disintegration of USSR and the rise of USA as a uniliteral world power in 1991. In the recent past, the rise of China in International Politics and the relative decline of US Supremacy instigated ‘New Great Power Competition.’ The researcher uses qualitative techniques to explain the ongoing Power Struggle between China and USA. The authors of this paper analysis the policies of both competitors they adopted to respond each other through the lenses of ‘Offensive Realism’.  The aim of the researchers is to highlight that, how China is influencing international Politics through its ‘Belt Road Initiative’ (BRI)?